Diamidines versus Monoamidines as Anti-Pneumocystis Agents: An in Vivo Study - El-Moukhtar Aliouat; Eduardo Dei-Cas; Anna Martinez; Jean Jacques Vanden Eynde; Sébastien Boutry; Isabelle Mahieu; Delphine Forge; Claire Pinçon; Dimitri Stanicki; Muriel Pottier; Nausicaa Gantois (MDPI AG, 2013)
Some compounds articulated around a piperazine or an ethylenediamine linker have been evaluated in vitro to determine their activity in the presence of a 3T6 fibroblast cell line and an axenic culture of Pneumocystis carinii, respectively. The most efficient antifungal derivatives, namely N,N'-bis(benzamidine-4-yl)ethane-1,2-diamine (compound 6, a diamidine) and N-(benzamidine-4-yl)-N'-phenylethane-1,2-diamine (compound 7, a monoamidine), exhibited no cytotoxicity and were evaluated in vivo in a rat model. Only the diamidine 6 emerged as a promising hit for further studies.